Monitoring power transformers oils deterioration using structured laser illumination planar imaging. (January 2018) - Regnima, Guy-Oscar; Betié, Amidou; Koffi, Thomas; Bagui, Olivier K.; Fofana, Issouf; Kouacou, Abaka; Zoueu, Jérémie
Highlights: Transformer oil extinction coefficient was measured using SLIPI. Extinction coefficient reveals the transformer oil aging. SLIPI has been successfully used as transformer oil diagnosis tool. Abstract: Reliable quality assessments of oils in power transformers are important as they provide valuable information regarding the proper functioning of transformers. Thus, an early and accurate diagnostic of power transformers oils can prevent potential failures of transformers. In this paper, an imaging technique known as Structured Laser Illumination Planar Imaging (SLIPI) was used to monitor the extinction coefficient μ e in various oil samples. The proposed technique offers the advantage of extracting the light intensity contribution from singly scattered photons and rejecting most of the light intensity from photons that have been scattered many times. This leads to more accurate and reliable measurement of the extinction coefficient μ e, in optically dense oil samples. The variation of the extinction coefficient was therefore determined as a function of oil aging. The results demonstrate that SLIPI is reliable as a practical measurement method for the diagnosis of power transformer oils and present an attractive solution, alternative to the conventional methods such as Dissolved Decay Products, Interfacial Tension and Turbidity.